Sistem Informasi Pengingat Jadwal General Check Up di Laboratorium Prima Medika Kudus Berbasis SMS Gateway & Email - Susilowati, Lita, Gunawan Ariyanto,ST. M. Compt Sc., Ph.D (2015)
Nowadays, SMS (Short Message Service) has been optimalized by people. SMS has been used for its large scope, and the charity and eficient of usage. SMS Gateway is two direct communication which is connecting operation computer systems with the communication tools plugged to send or receive SMS. In the Prima Medika laboratory Kudus has already builded the system of schedule remind general check up based on the Gateway and Email. The system is not only using SMS' reminder to remind check up schedule, but also using SMS autoreplay to take the line number of check up. The check up schedule reminder is not only sent by SMS, but also sent by Email. Beside, to take the line number will be delivered through SMS. The developing of this system is using PHP language program, saving the database using MySQL. Also, to build the SMS' application use SMS' Cloud. Based on the trying, there is a conclussion that the application can help the patience at Laboratory to remind the schedule of general check up and take the line number, also become one of the information media which is easy accesed by everyone.